The effect of Government investment and Private Investment on Economic Growth and Labor Absorption and Its Impact on Poverty Levels In The Province Of South Kalimantan - Riyadi, Slamet (Archives of Business Research, 2019)
High-quality economic growth is economic growth that can encourage industrialization, can create jobs as wide as possible and can encourage the performance of other sectors more efficiently and effectively, high economic growth accompanied by efficient and effective allocation of resources can be stimulus in development to improve people’s income so that it can reduce poverty. To reduce the level of poor people, of course, requires increased economic growth and equitable income distribution, rapid economic growth and not balanced with equity will lead to inequality between regions. There are several kinds of disparities that often block a society in its efforts to achieve prosperity, namely: (1) disparities between regions, (2) disparities between sectors, (3) disparities in the income distribution of the community. Studi aims to examine and analyze the effect of government investment and private investment on poverty levels through economic growth and labor absorption in South Kalimantan Province. The data analysis method used in this study is PLS to test the seven hypotheses formulated in this study. The conclusions of the results of this study are: 1) Government investment has a significant impact on economic growth. 2) Government investment does not have a significant impact on labor absorption. 3) Private investment does not have a significant impact on economic growth. 4) Private investment has a significant impact on labor absorption. 5) Economic growth has a significant impact on labor absorption. 6) Economic growth has a significant impact on reducing poverty levels. 7) Labor absorption has a significant impact on reducing poverty levels.